2021
DOI: 10.3389/fmicb.2020.604462
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and MicroRNA: Their Roles in the Host–Microbe Interactions

Abstract: Probiotics are widely accepted to be beneficial for the maintenance of the gut homeostasis – the dynamic and healthy interactions between host and gut microorganisms. In addition, emerging as a key molecule of inter-domain communication, microRNAs (miRNAs) can also mediate the host–microbe interactions. However, a comprehensive description and summary of the association between miRNAs and probiotics have not been reported yet. In this review, we have discussed the roles of probiotics and miRNAs in host–microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 144 publications
0
31
0
Order By: Relevance
“…The World Health Organisation’s defines probiotics as living microorganisms that confer a health benefit when administered in adequate amounts [ 72 ]. The effects of administering probiotics include the stabilization of the gut bacterial community and the restoration of “signature” of bacterial microbiota, which is a result of lowering the pH, producing bacteriocins, altering microRNA (miRNAs), competing with pathogens for certain nutrients and improving the gut barrier function [ 73 ]. Although the presented studies [ 26 , 27 ] seem to confer a promising perspective concerning the administration of oral probiotics for psoriasis, their limitations should also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation’s defines probiotics as living microorganisms that confer a health benefit when administered in adequate amounts [ 72 ]. The effects of administering probiotics include the stabilization of the gut bacterial community and the restoration of “signature” of bacterial microbiota, which is a result of lowering the pH, producing bacteriocins, altering microRNA (miRNAs), competing with pathogens for certain nutrients and improving the gut barrier function [ 73 ]. Although the presented studies [ 26 , 27 ] seem to confer a promising perspective concerning the administration of oral probiotics for psoriasis, their limitations should also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not fully understood, in a feedback mechanism that supports microbial dysbiosis of the gut, microbiota may influence host miRNAs, which in turn may suppress osteoblast development, posing a barrier to osteoporosis repair [152]. Of particular clinical interest may be the recent suggestion that miRNA and probiotics may play an essential role in host-microbe intercommunication [153]. Beyond the effects on miRNA, Uchida et al also considered a transcriptome-level analysis, finding transcripts for both anabolism and catabolism to be upregulated in the presence of commensal microbiota [154].…”
Section: Human Gut Microbiota: Role In Osteoporosis and Osteoclastogenesismentioning
confidence: 99%
“…miRNA is abnormally expressed in many diseases including UC, and has been proved to be involved in regulating the immune response of UC and the occurrence and development of colon tumors. Recent studies have also found that miRNA participates in the mutual regulation between host and intestinal flora (Aguilar et al, 2019;Dong et al, 2019;Zhao et al, 2021). These studies of miRNA have provided new insights into the molecular mechanism of UC.…”
Section: Overview Of Mirnasmentioning
confidence: 86%